2018
DOI: 10.1111/imr.12698
|View full text |Cite
|
Sign up to set email alerts
|

Insight into treatment ofHIVinfection from viral dynamics models

Abstract: SUMMARY The odds of living a long and healthy life with HIV infection have dramatically improved with the advent of combination antiretroviral therapy. Along with the early development and clinical trials of these drugs, and new field of research emerged called viral dynamics, which uses mathematical models to interpret and predict the time course of viral levels during infection and how they are altered by treatment. In this review, we summarize the contributions that virus dynamics models have made to unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 134 publications
(241 reference statements)
3
62
0
Order By: Relevance
“…However, in 20% of cases evolution toward more severe symptoms can take place leading to pneumonia or acute respiratory distress syndrome 4 . In other acute or chronic viral diseases (HIV, HCV, in uenza), the characterization of viral load kinetics has played an important role to understand the pathogenesis of the virus and design better antiviral drugs [5][6][7] . In the case of SARS-CoV-2, viral kinetics remain poorly characterized and its association with disease evolution is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…However, in 20% of cases evolution toward more severe symptoms can take place leading to pneumonia or acute respiratory distress syndrome 4 . In other acute or chronic viral diseases (HIV, HCV, in uenza), the characterization of viral load kinetics has played an important role to understand the pathogenesis of the virus and design better antiviral drugs [5][6][7] . In the case of SARS-CoV-2, viral kinetics remain poorly characterized and its association with disease evolution is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…4 Viral modeling in HIV and influenza. ( a ) Hill et al [ 73 ] described how an augmented viral dynamics model can be used to simulate antiretroviral therapy and the evolution of drug resistance in HIV. Uninfected cells ( U ) become infected ( I ) from infection by virus ( V ).…”
Section: Virusesmentioning
confidence: 99%
“…2.2, we expect that a small number of wild-type DNA gyrases should be enough for a bacterial cell to be sensitive, suggesting that phenotypic delay via gyrase dilution may be likely. Boe et al [47] report an unsatisfactory fit of their mutant number distribution data to the theoretical predictions of two different variants of the Luria-Delbrück model (the Lea-Coulson and Haldane models); in comparison to these models, Boe et al observed too many experiments yielding either no mutants or a high number of mutants (greater than 16), and a dearth of experiments resulting in intermediate mutant counts (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Qualitatively, this seems to be consistent with our expectations for the dilution model ( figure 4).…”
Section: Mutant Number Distributions May Support the Existence Of Phementioning
confidence: 99%
“…The emergence of resistance to drugs is a significant problem in the treatment of diseases such as cancer [1], and viral [2] and bacterial infections [3]. In infections with high pathogen load, the occurrence of de novo genetic mutations leading to resistance is a significant problem [4]; examples include endocarditis infections caused by Staphylococcus aureus [5,6], Pseudomonas aeruginosa infections of cystic fibrosis patients [7,8], as well as Burkholderia dolosa [9,4] infections.…”
Section: Introductionmentioning
confidence: 99%